2021
DOI: 10.3390/antiox10091365
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental and Lifestyle Use of Chromium on Male Fertility: Focus on Antioxidant Activity and Oxidative Stress

Abstract: Male reproductive tissues are strongly susceptible to several environmental and lifestyle stressors. In general, male reproductive health is highly sensitive to oxidative stress, which results in reversible and/or irreversible changes in testosterone-producing cells, spermatogenesis, and sperm quality. Chromium compounds are widely used in the +3 and +6 valence states, as food supplements, and in the industrial field, respectively. Chromium (III) compounds, i.e., Cr(III)-tris-picolinate, [Cr(pic)3], known as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 110 publications
0
21
0
1
Order By: Relevance
“…[40][41][42] Additionally, antioxidant treatment has been shown to have a positive effect on semen quality. 43,44 Moreover, several antioxidant or oxidant compounds were found to alleviate oxidative damage in sperm caused by FA exposure. 34,37 SOD and GSHPx are antioxidant enzymes protecting cells against oxidative damage, and MDA is a oxidation parameter measuring lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] Additionally, antioxidant treatment has been shown to have a positive effect on semen quality. 43,44 Moreover, several antioxidant or oxidant compounds were found to alleviate oxidative damage in sperm caused by FA exposure. 34,37 SOD and GSHPx are antioxidant enzymes protecting cells against oxidative damage, and MDA is a oxidation parameter measuring lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased oxidative stress in testicular tissue was found to affect the fertilization capacity of sperm cells (Aitken & Clarkson., 1987). Increasing evidence suggests that reactive oxygen species derived from testicular macrophages could have an impact on the steroidogenesis capacity of Leydig cells and germ cell death (Pereira et al, 2021). In clinical assessment, majority of infertile males have elevated seminal reactive oxygen species and sperm DNA damage, and also decreased fertilization capacity (Agarwal et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…According to this hypothesis, chromium (VI) itself is not a cytotoxic agent but rather an oxygen free radical generator via cellular reduction to chromium (VI). (28) The hydroxyl radical is thought to be formed when chromium reduction intermediates combine with hydrogen peroxide (HO). which may eventually damage biomolecules like proteins, DNA, and membrane lipids, affecting cellular functioning and cell integrity As a result, an antioxidant research of C. melo L fruit aqueous extract indicated that it reduced lipid peroxide by 81 percent in the liver and 77 percent in the kidney when compared to their respective individuals.…”
Section: Discussionmentioning
confidence: 99%